Non Linear Optical Properties of Silver Nanoparticles - Sadeq, Zainab Sabeeh (Iraqi Journal of Science, 2022)
In the present work, a Z-scan technique was used to study the nonlinear optical properties, represented by the nonlinear refractive index and nonlinear absorption coefficients of the Ag nanoparticles. In this technique, a pulsed second harmonic Nd :YAG laser at wavelength 532 nm was used. The results show that the nonlinear refractive index and nonlinear absorption coefficients of the Ag nanoparticles are found to be dependent on the size these nanoparticles.